2013
DOI: 10.1177/000313481307900708
|View full text |Cite
|
Sign up to set email alerts
|

The Green Operating Room: Simple Changes to Reduce Cost and Our Carbon Footprint

Abstract: Generating over four billion pounds of waste each year, the healthcare system in the United States is the second largest contributor of trash with one-third produced by operating rooms. Our objective is to assess improvement in waste reduction and recycling after implementation of a Green Operating Room Committee (GORC) at our institution. A surgeon and nurse-initiated GORC was formed with members from corporate leadership, nursing, anesthesia, and OR staff. Initiatives for recycling opportunities, reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 14 publications
0
95
0
14
Order By: Relevance
“…Furthermore, a formal cost analysis should be performed both with our data and that of other services. From an environmental perspective, much has been written about the amount of waste produced from the operating theatre [ 3 , 4 ]. The simple act of shrinking the contents of trays, and combining multiple trays into fewer trays, would immediately reduce the waste produced from the tray wrappings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a formal cost analysis should be performed both with our data and that of other services. From an environmental perspective, much has been written about the amount of waste produced from the operating theatre [ 3 , 4 ]. The simple act of shrinking the contents of trays, and combining multiple trays into fewer trays, would immediately reduce the waste produced from the tray wrappings.…”
Section: Discussionmentioning
confidence: 99%
“…Although suitable for large volumes, incineration produces toxic pollutants such as heavy metals, dioxins, acid gases, and hydrogen chloride ( Yang et al., 2009 ). Consequently, pre-COVID-19, besides incineration, reducing or preventing the volume of wastes in both categories is also shaped by the adoption of green purchasing practices ( Wormer et al., 2013 ). While this may help in the short term, a holistic approach to confronting this problem is the adoption of CE, which can facilitate the shift towards eco-efficient HCI, starting with lifecycle evaluations of medical products to the proposal for re-usable medical instruments ( Cimprich et al., 2019 ; De Soete et al., 2017 ; Penn et al., 2012 ).…”
Section: Opportunities For Circular Economy Post Covid-19mentioning
confidence: 99%
“…The majority of hospital RMW is produced in the operating room (OR), and it considerably consists of disposable packaging and wrapping materials for the sterilization of surgical instruments [ 4 ]. After examining the composition of this kind of waste, we found that a number of items had a recycling mark indicating that they were recyclable.…”
mentioning
confidence: 99%